Performa dan Kualitas Telur Puyuh Jepang yang Diberi Tepung Daun Kayambang (Salvinia molesta DS Mitch) dalam Pakan - Suci, Dwi Margi; Kurnia Dewi, Fitriana (Universitas Djuanda, 2025)
Kayambang (Salvinia molesta) is an aquatic plant that has the potential to be an alternative feed for poultry. The aim of this research was to evaluated the use of kayambang leaves meal as a feed ingredient for layer quail. One hundred twenty day-old quail (DOQ) that reared for 7 weeks. The treatments of the using kayambang leaves meal as much as 2%, 4% and 6% in the ration. The experimental design used completely randomized design (CRD) with 4 treatments and 5 replications. The results showed that the treatments was given in the ration not significantly affected (P<0.05) on consumption, feed conversion, and egg production, egg yolk, egg weight, and thick of shell. In can be conncluded 3% of kayambang leaves meal can be used as an alternative feed on the quail layer ration.